Use of Opportunistic Clinical Data and a Population Pharmacokinetic Model to Support Dosing of Clindamycin for Premature Infants to Adolescents. Issue 4 (20th June 2014) - Gonzalez, D; Melloni, C; Yogev, R; Poindexter, B B; Mendley, S R; Delmore, P; Sullivan, J E; Autmizguine, J; Lewandowski, A; Harper, B; Watt, K M; Lewis, K C; et al.
<x xml:space="preserve">Abstract</x> Clindamycin is commonly prescribed to treat children with skin and skin‐structure infections (including those caused by community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA)), yet little is known about its pharmacokinetics (PK) across pediatric age groups. A population PK analysis was performed in NONMEM using samples collected in an opportunistic study from children receiving i.v. clindamycin per standard of care. The final model was used to optimize pediatric dosing to match adult exposure proven effective against CA‐MRSA. A total of 194 plasma PK samples collected from 125 children were included in the analysis. A one‐compartment model described the data well. The final model included body weight and a sigmoidal maturation relationship between postmenstrual age (PMA) and clearance (CL): CL (l/h) = 13.7 × (weight/70)0.75 × (PMA3.1/(43.63.1 + PMA3.1)); V (l) = 61.8 × (weight/70). Maturation reached 50% of adult CL values at ~44 weeks PMA. Our findings support age‐based dosing. Clinical Pharmacology & Therapeutics (2014); 96 4, 429–437. doi:10.1038/clpt.2014.134